2022
DOI: 10.1007/s12325-022-02069-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Omidenepag Isopropyl 0.002% Ophthalmic Solution: A Retrospective Analysis of Real-World Data in Japan

Abstract: Introduction: This study aimed to clarify the efficacy and safety of omidenepag isopropyl (OMDI) in a retrospective, real-world, multicenter setting. Methods: A retrospective medical chart review of patients with glaucoma and ocular hypertension receiving OMDI from November 2018 to November 2019 with at least 12 weeks of follow-up was conducted in 11 eye clinics in Japan. The participants were categorized into three therapy groups, designated the naı ¨ve monotherapy, switching monotherapy, and concomitant ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…More recently, a novel non-PG EP2 receptor-selective agonist, omidenepag isopropyl ester (OMDI), potently and efficaciously reduced IOP in rabbits, dogs, and lasered OHT Cynomolgus monkeys [ 73 ]. Importantly, OMDI potently and efficaciously lowered and controlled IOP as effectively as latanoprost in human subjects suffering from OHT, open-angle glaucoma (OAG), primary angle-closure glaucoma (PACG), and secondary glaucoma (see recent reviews [ 34 , 80 , 81 ]). Thus, it appears that EP2 receptor agonists can be useful in treating various forms of OHT induced by different mechanisms and under different experimental and clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a novel non-PG EP2 receptor-selective agonist, omidenepag isopropyl ester (OMDI), potently and efficaciously reduced IOP in rabbits, dogs, and lasered OHT Cynomolgus monkeys [ 73 ]. Importantly, OMDI potently and efficaciously lowered and controlled IOP as effectively as latanoprost in human subjects suffering from OHT, open-angle glaucoma (OAG), primary angle-closure glaucoma (PACG), and secondary glaucoma (see recent reviews [ 34 , 80 , 81 ]). Thus, it appears that EP2 receptor agonists can be useful in treating various forms of OHT induced by different mechanisms and under different experimental and clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution with PGA or non-PGA drugs may be effective in lowering IOP in poor or non-responders [66,139]. OMPI is effective in NTG [140] and secondary glaucoma [141].…”
Section: Choice Of Therapymentioning
confidence: 99%
“…Clearly, the higher the baseline IOPs, the greater the efficacy of OMDI 0.002% ( Figure 15 B). More recent studies indicated that OMDI may also be therapeutically useful in Japanese patients with secondary glaucomas and primary angle-closure glaucoma ( Figure 16 ; [ 211 , 212 , 213 ]). This is where a relatively fast onset of action of OMDI may be beneficial, as identified from the monkey studies [ 127 , 187 , 188 ].…”
Section: Recently Approved Drug-based Therapeutics For Oag/oht Treatmentmentioning
confidence: 99%
“…Various animal-based and clinical studies have also demonstrated that OMDI can be combined with other IOP-lowering drugs to obtain additional efficacy [ 187 , 207 , 208 , 214 ] ( Figure 13 and Figure 15 B). Such adjunctive therapy will prove useful for patients with many types of glaucoma [ 212 ]. Furthermore, recent clinical studies involving OMDI 0.002% demonstrated its beneficial ocular hypotensive properties in patients suffering from not only OHT and OAG, but it also lowered IOP significantly in NTG and ACG patients as well over a 4- week trial period ( Figure 16 ) [ 127 , 212 , 213 ].…”
Section: Recently Approved Drug-based Therapeutics For Oag/oht Treatmentmentioning
confidence: 99%
See 1 more Smart Citation